The post-colonial studies reader - Ashcroft, Bill; Griffiths, Gareth; Tiffin, Helen (Routledge, 1995)
The Post-Colonial Studies Reader is the most comprehensive selection of key texts in post-colonial theory and criticism yet compiled. This collection covers a huge range of topics, featuring nearly ninety of the discipline's most widely read works. The Reader's 90 extracts are designed to introduce the major issues and debates in the field of post-colonial literary studies. This field itself, however, has become so varied that no collection of readings could encompass every voice which is now giving itself the name "post-colonial." The editors, in order to avoid a volume which is simply a critical canon, have selected works representing arguments with which they do not necessarily agree, but rather which above all stimulate discussion, thought and further exploration. Post-colonial "theory" has occurred in all societies into which the imperial force of Europe has intruded, though not always in the official form of theoretical text. Like the description of any other field the term has come to mean many things, but this volume hinges on one incontestable phenomenon: the "historical fact"of colonialism, and the palpable consequences to which this phenomenon gave rise. The topic involves talk about experience of various kinds: migration, slavery, suppression, resistance, representation, difference, race, gender, place, and reaction to the European influence, and about the fundamental experiences of speaking and writing by which all these come into being. In compiling this reader, the editors have sought to stimulate people to ask: "How might a genuinely post-colonial literary enterprise proceed?" The fourteen sections include: Issues and Debates; Universality and Difference; Textual Representation and Resistance; Postmodernism and Post-Colonialism; Nationalism; Hybridity; Ethnicity and Indigenity; Feminism and Post-Colonialism; Language; The Body and Performance; History; Place; Education; and Production and Consumption. Contributors include many of the leading post-colonial theorists and critics–such as Franz Fanon, Chinua Achebe, Gayatri Chakravorty Spivak, Ngugi wa Thiong'o, Homi Bhabba, Derek Walcott, Edward Said, and Trinh T. Minh-ha–in addition to a number of the discourse's newer voices. The Post-Colonial Studies Reader will prove an authoritative compilation, representing an invaluable contribution to the study of post-colonial theory and criticism.
Keywords: 1900-1999; 1990-1999; approches et analyses; cours; discipline; fem1000; féminisme décolonial; histoire et politique; littérature; premier cycle; périodes historiques; thématiques; études culturelles; études littéraires

A diplomacy of the oppressed: New directions in international feminism - Ashworth, Georgina (Zed Books, 1995)
Les contributrices abordent les problèmes du mouvement international des femmes, tels que la résolution des conflits; la violence; zones de libre-échange ; l'environnement; culture et identité nationale; santé; les média; droits humains; et l'emploi, en mettant l'accent sur la situation des femmes dans toutes les régions du monde. Destiné aux étudiants en études féministes, en sciences politiques et en études du développement
Keywords: 1900-1999; anthologie; approches et analyses; conflit; coopérative internationale; cours; discipline; fem1000; genre; histoire; histoire et politique; identités LGBTQIA2+; inégalités; militance; mouvements des femmes*; mouvements féministes; premier cycle; périodes historiques; science politique; science politique et droit; sciences humaines; systèmes d'oppressions; thématiques

America's working women: A documentary history, 1600 to the present - Baxandall, (1939- ...)., Rosalyn Fraad; Gordon, Linda; Reverby, Susan (W.W. Norton, 1995)
A landmark work when it appeared in 1976, America's Working Women helped form the field of women's studies and transform labor history. Now the authors have enlarged the dimensions of this important anthology; more than half the selections and all the introductory material are new. Spanning the years from 1600 to the present, selections from diaries, popular magazines, historical works, oral histories, letters, songs, poetry, and fiction show women's creativity in supporting themselves, their families, and organizations or associations. Slave women recall their field work, family work, and sabotage. We see Indian women farming, and we also see the white culture coercing Indian women to give up farming. We see women in industry playing a central part in the union movement while facing the particular hazards of women's jobs and working conditions. New selections show the historical origins of today's important issues: sexual harassment, equal pay, "sex work," work in the underground economy, work in the home, and shift work. With an expanded focus on women from all racial and ethnic backgrounds and regions, America's Working Women grounds us in the battles women have fought and the ones they are in the process of winning.
Accessible en ligne : https://archive.org/details/isbn_9780393312621
Keywords: 1600-1699; 1700-1799; 1800-1899; 1900-1999; amériques; approches et analyses; cours; discipline; discours dominant; droits des femmes*; famille; his4443; histoire; histoire des femmes*; histoire et politique; inégalités; premier cycle; périodes historiques; racisme; racisme systémique; rapports sociaux de sexe; régions géographiques; sciences humaines; système colonial; systèmes d'oppressions; thématiques; travail; travail des femmes*; états-unis

Mapping desire: geographies of sexualities - Bell, David; Valentine, Gill (Routledge, 1995)
This is the first book to explore sexualities from a geographical perspective. The nature of place and notions of space are of increasing centrality to cultural and social theory. Mapping Desire presents the rich and diverse world of contemporary sexuality, exploring how the heterosexual body has been appropriated and resisted on the individual, community and city scales. The geographies presented here range across Europe, America, Australasia, Africa, the Pacific and the imaginary, cutting across city and country and analysing the positions of gay men, lesbians, bisexuals and heterosexuals. The contributors ring different interests and approaches to bear on theoretical and empirical material from a wide range of sources. The book is divided into four sections: cartographies/identities; sexualised spaces: global/local; sexualised spaces: local/global; sites of resistance. Each section is separately introduced. Beyond the bibliography, an annotated guide to further reading is also provided to help the reader map their own way through the literature.
Le texte de Binnie, Jon. 1995. « Trading places : consumption, sexuality and the production of queer space. » figure dans la bibliographie du cours SOC2014.
Keywords: LGBTQIA2+; approches et analyses; cours; discipline; géographie; hétéronormativité; hétérosexisme; premier cycle; queer; sciences humaines; sexologie; sexualité; soc2014; systèmes d'oppressions; thématiques

L’éducation des enfants dans Le Chrysanthème et le sabre - Benedict, Ruth Fulton; Mécréant, Lise (Le Chrysanthème et le sabre, 1995)
Cet essai, écrit à distance, sur commande de l'Office of War Information, par une femme qui n'était jamais allée au Japon et en ignorait la langue, pour servir de manuel aux forces d'occupation américaines, réussit la gageure de demeurer, de l'avis général des Japonais, l'un des grands livres que l'on ait écrit sur eux. Des articles et des ouvrages ont, après lui, été publiés qui réfutent, complètent, approfondissent, réapprécient les interprétations de Ruth Benedict. Ces débats lui ont conféré la place d'une référence classique." Ce livre traite des habitudes qui paraissent naturelles et que nul ne songerait à remettre en cause au Japon. Il traite des situations où tout Japonais peut compter sur la courtoisie et de celles où il se sent honteux, des circonstances où il éprouve de l'embarras, de ce qu'il exige de lui-même." On y parle des règles de hiérarchie, de bienséance, de l'éducation des enfants, de morale sexuelle, de politique économique ...
Section: 355 p. ; 17 cm.
Keywords: 1900-1999; 1990-1999; approches et analyses; asie; cours; discipline; japon; premier cycle; périodes historiques; régions géographiques; sciences humaines; soc3113; sociologie; thématiques

Lettre d'une Africaine à ses soeurs occidentales - Beyala, Calixthe (Spengler, 1995)
A travers le regard d'une femme africaine sur ses sœurs occidentales, nos découvrons avec horreur la condition des femmes d'Afrique qui n'a guère changé en dépit des progrès. Qu'il s'agisse du non-accès à l'éducation dont sont encore privées beaucoup de petites filles, de l'excision (mutilation du plaisir chez la femme) ou de al dépendance économique, sociale et culturelle à l'homme, Calixthe l'Africaine dresse un noir tableau des combats qu'il reste à mener. L'autre part du discours à trait à "l'endormissement" de la femme occidentale ; ou plutôt, selon Calixthe, la femme a été endormie par l'homme qui depuis plusieurs années s'est transformé en agneau pour mieux renaître en loup. Calixthe Beyala lance un signal d'alarme à ses "sœurs" ne baissez pas les bras, tout reste à faire ; énormément chez nous en Afrique, beaucoup chez vous en Occident. Ecrit dans le style vif et alerte qui al caractérise, l'ouvrage de Calixthe ne recule pas devant les mots pour se faire entendre des femmes, et certainement, les réveiller. Calixthe Beyala est camerounaise. Ecrivain, elle vit et travaille en France. Mère de deux enfants, elle a la charge de nombreux enfants au Cameroun. Elle a publié plusieurs romans très remarqués dont "C'est le soleil qui m'a brûlée", premier roman bouleversant en hommage à sa sœur morte à l'âge de 23 ans, symbole de la lutte que doit sans cesse mener la femme africaine, "Le petit prince de Belleville", "Maman a un amant" et "cet automne "Assèze l'Africaine". Le style et le caractère puissant de son œuvre font d'elle une des toutes premières romancières africaines.
Section: 155, [4] pages ; 21 cm
Keywords: afrique; afro-féminisme; approches et analyses; arts; cours; discipline; droits des femmes*; féminisme africain; lit2815; premier cycle; régions géographiques; thématiques; études littéraires

Les relations amoureuses entre les femmes du XVIe au XXe siècle. Essai historique. - Bonnet, Marie-Joe (Odile Jacob, 1995)
Voici la première histoire de l'amour entre les femmes qui, sur cinq siècles, de la Renaissance à nos jours, tienne compte à la fois du regard extérieur des hommes et de l'approche des lesbiennes elles-mêmes. Pour la première fois, aussi, une analyse à long terme est proposée qui dégage une évolution des moeurs, des mentalités et de la place des femmes dans la société. Jusqu'à présent, en effet, l'histoire des femmes occultait l'amour entre femmes, alors que les lesbiennes ont joué un rôle prépondérant dans les mouvements progressistes politiques et artistiques. Unique en son genre par son érudition, son approche pluridisciplinaire, ses mises en perspective originales et la période considérée, cet essai s'impose déjà comme un ouvrage de référence.
Première publication: 1981
Keywords: approches et analyses; corps; cours; cycles supérieurs; discipline; droits des femmes*; europe; fem1000; fem7000; france; histoire; histoire des femmes*; histoire et politique; hétérosexisme; identités; identités LGBTQIA2+; invisibilités; lesbianisme; lit3220; premier cycle; régions géographiques; sciences humaines; sexualité; systèmes d'oppressions; thématiques

Fémininmasculin: le sexe de l'art. - Centre Georges Pompidou. (Gallimard/Electa, 1995)
Premier chapitre du Passage du siècle (les grands bilans que le Centre Georges Pompidou proposera en 1996 et 1997), cette exposition renoue avec des expériences décisives comme par exemple "Eros", organisée en 1959 par Marcel Duchamp et André Breton. A travers le titre "Féminin - Masculin, le sexe de l'art" s'exprime un double enjeu : celui de réhabiliter le terme dévalué d'une opposition inscrite dans la tradition des couples hiérarchiques de la pensée occidentale (forme/matière, vérité/mensonge, être/paraître, profondeur/surface, etc.) ; celui de montrer qu'au delà d'un simple sujet-motif artistique, le sexe est partie prenante des processus de l'art lui-même. L'ambition de cette exposition est de montrer, en dehors de toute approche chronologique, comment les productions artistiques du XXe siècle n'ont eu de cesse de venir brouiller les fatalités biologiques, anatomiques et culturelles traditionnellement liées au sexe. Aborder l'art dans la perspective de la différence sexuelle, ce n'est pas mécaniquement opposer un art "masculin" à un art "féminin", mais tenter de donner à voir comment les oeuvres se trouvent traversées par cette question, au-delà du sexe - du genre - des artistes qui les produisent. Féminin - Masculin, le sexe de l'art montrera aussi la coexistence dans ce siècle de deux généalogies artistiques concernant le sexe. L'une, à partir de Picasso, s'inscrit dans la tradition classique de la différence des sexes, conçue comme une opposition dialectique et organique du masculin et du féminin. L'autre, à partir de Marcel Duchamp, inaugure un nouveau type de relations, selon une logique asymétrique, faisant circuler les intensités masculines et féminines sur un mode proliférant qui opère une déterritorialisation des entités anatomiques, identificatoires et formelles. Les artistes de la jeune génération (tant américaine qu'européenne) semblent très sensibles à cette manière de déstabiliser les polarités traditionnelles du masculin et du féminin, mettant en oeuvre de nouvelles configurations éthiques et formelles qui se situent au-delà de la différence sexuelle, et en cela se distinguant en radicalement des positions identitaires des années 70.
Keywords: 1900-1999; LGBTQIA2+; amériques; arts; arts visuels et médiatiques; cours; discipline; europe; exposition; har4600; histoire et politique; identités LGBTQIA2+; premier cycle; périodes historiques; régions géographiques; sexualité; thématiques; états-unis

Moi, Tituba sorcière –: noire de Salem - Condé, Maryse; De Serres, Murielle; Thérien, Michel; Jean, Julie (Beauchemin, 1995)
Fille d'une esclave violée par un marin anglais à bord d'un vaisseau négrier, Tituba, née à la Barbade, est initiée aux pouvoirs surnaturels par Man Yaya, guérisseuse et faiseuse de sorts. Son mariage avec John Indien l'entraîne à Boston puis au village de Salem, au service du révérend Samuel Parris. Elle est emprisonnée à la suite du procès des sorcières de Salem en 1692.
Section: 223 p., [16] p. de planches : ill. en coul.
Keywords: afro-féminisme; amériques; approches et analyses; arts; barbade; caraïbes; cours; discipline; féminismes noirs; histoire et politique; lit2815; premier cycle; roman; régions géographiques; système colonial; systèmes d'oppressions; thématiques; états-unis; études littéraires

Sexy bodies: the strange carnalities of feminism - Grosz, E. A.; Probyn, Elspeth (Routledge, 1995)
Are bodies sexy? How? In what sorts of ways? Sexy Bodies investigates the production of sexual bodies and sexual practices, of sexualities which are dyke, bi, transracial, and even hetero. It celebrates lesbian and queer sexualities but also explores what runs underneath and within all sexualities, discovering what is fundamentally weird and strange about all bodies, all carnalities. Looking at a pleasurable variety of cultural forms and texts, the contributors consider the particular charms of girls and horses, from National Velvet to Marnie; discuss figures of the lesbian body from vampires to tribades to tomboys; uncover 'virtual' lesbians in the fiction of Jeanette Winterson; track desire in the music of legendary Blues singers; and investigate the ever-scrutinised and celebrated body of Elizabeth Taylor. The collection includes two important pieces of fiction by Mary Fallon and Nicole Brossard. Sexy Bodies makes new connections between and amongst bodies, cruising the borders of the obscene, the pleasurable, the desirable and the hitherto unspoken rethinking sexuality anew as deeply and strangely sexy.
Keywords: LGBTQIA2+; approches et analyses; corps; cours; féminisme pop; identités LGBTQIA2+; lesbianisme; lit4700; premier cycle; queer; ressource en ligne; sexualité; thématiques

Gender articulated: language and the socially constructed self - Hall, Kira; Bucholtz, Mary (Routledge, 1995)
Gender Articulated is a groundbreaking work of sociolinguistics that forges new connections between language-related fields and feminist theory. Refuting apolitical, essentialist perspectives on language and gender, the essays presented here examine a range of cultures, languages and settings. They explicitly connect feminist theory to language research. Some of the most distinguished scholars working in the field of language and gender today discuss such topics as Japanese women's appropriation of "men's language," the literary representation of lesbian discourse, the silencing of women on the Internet, cultural mediation and Spanish use at New Mexican weddings and the uses of silence in the Anita Hill-Clarence Thomas hearings.
Donné en lecture au cours LIN2685, Hall, Kira, Lip Service on the Fantasy Lines, pp321-342.
Keywords: LGBTQIA2+; approches et analyses; cours; discipline; identités LGBTQIA2+; langage; lin2685; linguistique; maternité; premier cycle; queer; sciences humaines; sociolinguistique; thématiques; études de genres

XXX: a woman's right to pornography - McElroy, Wendy (St. Martin's Press, 1995)
An unconventional argument for the preservation of pornography asserts that pornography can serve to benefit the feminist movement and promote sexual freedom for women, and explores the historical relationship between women and pornography.
Section: xi, 243 pages ; 22 cm
Keywords: corps; cours; droits des femmes*; pornographie; premier cycle; sex1911; sexualité; thématiques

Un sujet inclassable? approches sociologiques, littéraires et juridiques des homosexualités - Mendès-Leite, Rommel ("Cahiers Gai-Kitsch-Camp, 1995)
Section: 211 pages : illustrations, couv. illustrations en couleur ; 21 cm
Keywords: 1900-1999; LGBTQIA2+; approches et analyses; cours; discipline; discours dominant; droits; europe; france; histoire et politique; hétéronormativité; hétérosexisme; identités LGBTQIA2+; inégalités; lesbianisme; premier cycle; périodes historiques; queer; régions géographiques; shm4000; systèmes d'oppressions; thématiques

Thunder in my soul: a Mohawk woman speaks - Monture-Angus, Patricia (Fernwood Publishing, 1995)
"This book contains the reflections of one Mohawk woman and her struggles to find a good place to be in Canadian society. The essays, written in enjoyable and accessible language, document the struggles against oppression that Aboriginal people face, as well as the success and change that have come to Aboriginal communities. It speaks to both the mind and the heart."–Résumé de l'éditeur.
Section: x, 273 pages ; 23 cm
Keywords: 1900-1999; 1960-1969; 1970-1979; 1980-1989; 1990-1999; amériques; approches et analyses; canada; cours; discipline; féminisme autochtone; histoire et politique; inégalités; mohawk; pol4105; premier cycle; périodes historiques; régions géographiques; science politique; science politique et droit; sciences de l'éducation; système colonial; systèmes d'oppressions; thématiques

Of woman born: Motherhood as experience and institution - Rich, Adrienne (Norton, 1995)
Adrienne Rich's influential and landmark investigation concerns both the experience and the institution of motherhood. The experience is her own—as a woman, a poet, a feminist, and a mother—but it is an experience determined by the institution, imposed on all women everywhere. She draws on personal materials, history, research, and literature to create a document of universal importance. Dans Of Woman Born , initialement publié en 1976, la poétesse et féministe influente Adrienne Rich examine les systèmes patriarcaux et les institutions politiques qui définissent la maternité. En explorant sa propre expérience - en tant que femme, poète, féministe et mère - elle trouve que l'acte de materner est à la fois déterminé par et distinct de l'institution de la maternité telle qu'elle est imposée à toutes les femmes partout dans le monde
Première édition: 1976
Keywords: 1900-1999; 1970-1979; amériques; approches et analyses; corps; cours; discours dominant; fem1000; maternité; premier cycle; périodes historiques; régions géographiques; santé; systèmes d'oppressions; thématiques; théories féministes; états-unis

Démocratie et représentation - Riot-Sarcey, Michèle (Kimé, 1995)
La représentation politique est aujourd’hui en crise : partout en Europe, la légitimité des représentants est contestée, sans pour autant que la démocratie, en son principe, soit mise en cause. A partir de ce constat, des chercheurs des différentes disciplines ont questionné la représentation dans son actualité politique et dans sa formation historique. L’usage de la représentation, la délégation d’autorité qu’elle suppose, la violence qu’elle engendre, la domination qu’elle implique, la pratique démocratique qu’elle présuppose ont été soumis à examen par les intervenants au colloque organisé par le Centre Culturel de l’Albigeois. Les disfonctionnements et les apories d’une démocratie, longtemps considérés comme une donnée perfectible, se révèlent comme un simple produit des règles d’un système exclusif, qui contribuent largement à tenir à l’écart des pouvoirs et des lieux de représentation politiques les femmes comme la grande majorité d’une population, par ailleurs de plus en plus politisée.
Keywords: 1900-1999; 1990-1999; approches et analyses; cours; discipline; fem1000; interdisciplinarité; occident; premier cycle; périodes historiques; représentation politique; science politique; science politique et droit; sciences humaines; théories féministes

Defending pornography: free speech, sex, and the fight for women's rights - Strossen, Nadine (Scribner, 1995)
This book examines a key question that has divided feminists for decades: is censoring pornography good or bad for women? The book makes a powerful case that increasing government power to censor sexual expression, beyond the limits that the First Amendment sensibly permits (for example, outlawing child pornography) would do more harm than good for women and others who have traditionally been marginalized due to sex or gender. The book explains how the very anti-porn laws pushed by some feminists have led to the censorship of LGBTQ+ and feminist works, and it examines the startling connections between anti-porn feminists and right-wing fundamentalists. The book lays out the multiple current assaults on sexual expression, which continue to come from across the ideological spectrum. It shows that freedom for such expression remains an essential prerequisite for the equality, safety, and dignity of women and sexual/gender minorities.
Section: 320 p. : ill. ; 22 cm
Keywords: amériques; cours; discipline; droit; droits des femmes*; liberté d'expression; pornographie; premier cycle; régions géographiques; science politique et droit; sex wars; sex1911; thématiques; états-unis